STOP 101: A Phase 1, Randomized, Open‐Label, Comparative Bioavailability Study of INP104, Dihydroergotamine Mesylate (DHE) Administered Intranasally by a I123 Precision Olfactory Delivery (POD®) Device, in Healthy Adult Subjects. Issue 3 (19th January 2019) - Shrewsbury, Stephen B.; Jeleva, Maria; Satterly, Kelsey H.; Lickliter, Jason; Hoekman, John
Abstract : Objective: Investigate the safety and pharmacokinetics (PK) of INP104, intranasal dihydroergotamine mesylate (DHE) administered via a Precision Olfactory Delivery (POD ® ) device, (Impel NeuroPharma, Seattle, WA) vs intravenous (IV) DHE and DHE nasal spray (Migranal ® ) in healthy adult subjects. Methods: This was a Phase 1, open‐label, randomized, single‐dose, 3‐period, 3‐way crossover study. Subjects received a single dose of A) INP104 1.45 mg (a drug‐device combination product composed of DHE and the I123 POD device); B) DHE 45 ® Injection (IV) 1.0 mg; and C) DHE by Migranal ® Nasal Spray 2.0 mg. Plasma levels of DHE and the major bioactive metabolite, 8′OH‐DHE, were measured, and PK parameters were determined for both. Comparative bioavailability (BA) was assessed by calculating the ratio of the geometric means between treatments for Cmax and AUC0‐inf on the ln‐transformed data. Safety was assessed from adverse events, vital signs, electrocardiograms, and clinical laboratory values. Results: Thirty‐eight subjects were enrolled, 36 were dosed with at least 1 IP and 27 were included in the evaluation of PK and comparative BA. DHE plasma levels following INP104 1.45 mg administration reached 93% of Cmax by 20 minutes and were comparable to IV DHE 1.0 mg by 30 minutes (1219 ng/mL for INP104 vs 1224 ng/mL for IV DHE), which was the Tmax for INP104. From 30 minutes onward, DHE levels for INP104 closely matched those of IV DHE to 48 hours, the last time point measured. In comparison, the Cmax for Migranal was 299.6 pg/mL (approximately 4‐fold less than INP104) and occurred at 47 minutes, 17 minutes later than INP104. Plasma DHE AUC0‐inf were 6275, 7490, and 2199 h*pg/mL for INP104, IV DHE, and Migranal, respectively. Variability (coefficient of variation [CV%]) for Cmax and AUC0‐inf for INP104 compared to Migranal indicated more consistent delivery with INP104. In the BA comparison using the PK population (subjects who had received all 3 treatments), the ratios of geometric means (percent) for Cmax and AUC0‐inf were 7.9% and 74.2%, respectively, for INP104: IV DHE, and 445% and 308% for INP104: Migranal. Mean plasma concentration profiles for 8′‐OH‐DHE were proportionately lower and followed a similar profile to the parent compound, regardless of route of administration (IN vs IV) or delivery system (Migranal vs INP104). Treatment emergent AEs (TEAEs), of mostly mild intensity, were reported by 15/31 (48.4%), 21/32 (65.6%), and 14/34 (41.2%) subjects after INP104, IV DHE, and Migranal, respectively. Treatment‐related TEAEs occurred in 6/31 (19.4%), 16/32 (50.0%), and 4/34 (11.8%) subjects after INP104, IV DHE, and Migranal, respectively. Conclusion: INP104 met the predefined statistical criteria for comparative bioavailability with IV DHE and Migranal. The shorter time to reach Cmax and at 4 times the plasma concentration of DHE in comparison to Migranal combined with a favorable tolerability profile support further investigation of INP104 as an effective, well tolerated, and non‐invasive treatment for acute episodic migraine.